2012
DOI: 10.1212/wnl.0b013e318266fcc5
|View full text |Cite
|
Sign up to set email alerts
|

MRI abnormalities following febrile status epilepticus in children

Abstract: This prospective study demonstrates that children with FSE are at risk for acute hippocampal injury and that a substantial number also have abnormalities in hippocampal development. Follow-up studies are in progress to determine the long-term outcomes in these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
186
4
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(210 citation statements)
references
References 35 publications
13
186
4
4
Order By: Relevance
“…This is in accordance with our study in adults with TLE where FLAIR hyperintensity in the parahippocampal gyrus was modulated by a history of febrile convulsions. Furthermore, the results from a prospective imaging study in children have shown visible T2 hyperintensity in the adjacent ipsi‐lesional temporal neocortex following febrile status epilepticus49 and suggests a particular vulnerability of the ipsilateral temporal pole to early insults. However, the causal relationship between febrile seizures and the subsequent development of mesial temporal lobe epilepsy is still unclear 50…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with our study in adults with TLE where FLAIR hyperintensity in the parahippocampal gyrus was modulated by a history of febrile convulsions. Furthermore, the results from a prospective imaging study in children have shown visible T2 hyperintensity in the adjacent ipsi‐lesional temporal neocortex following febrile status epilepticus49 and suggests a particular vulnerability of the ipsilateral temporal pole to early insults. However, the causal relationship between febrile seizures and the subsequent development of mesial temporal lobe epilepsy is still unclear 50…”
Section: Discussionmentioning
confidence: 99%
“…Ancak afebril nöbet gelişimi açısından yüksek riske sahip; anormal nöromotor gelişim, fokal veya uzamış konvülziyon öykü-sü bulunan hastalarda taburculuğunda manyetik rezonans görüntüleme istenebilir. 48 Diazepam: Yüksek oranda yağda eriyen ve hızla beyine geçiş gösteren bir ilaçtır. GABA'erjik sinaptik inhibisyonun etkisini arttırarak beynin pek çok bölgesinde kritik nöronların ateşlen-mesini azaltır.…”
Section: Etyolojiunclassified
“…In the FEBSTAT study, a longitudinal study to try and elucidate the pathogenic link between FS and late development of epilepsy, 11.5 % of children presenting with prolonged (>30 min) febrile status had increased or equivocal T 2 signal in the hippocampus and more widespread in the temporal lobe, compared with none among children with simple febrile seizures [85]. T2W hippocampal signal abnormality was associated with focal EEG slowing or attenuation suggestive of acute hippocampal injury [86].…”
Section: Signal Changesmentioning
confidence: 99%
“…In the FEBSTAT study, developmental abnormalities of the hippocampus (hippocampal malrotation being the most common) were seen in the group of children with prolonged FS, suggestive of a possible predisposition to the initial epileptogenic insult [85]. Seizure-generating hypothalamic hamartomas appear to always have a connection to one or both mammillary bodies [91].…”
Section: Volumetric and Morphological Analysismentioning
confidence: 99%